FIGHT AGAINST MALARIA AND RONALD ROSS - Lahiry, D. (SCHOOL SCIENCE, 2013)
Malaria has been one of the biggest killer diseases in the history of humanity. Not cholera or plague, nor to speak of AIDS. It is estimated that during the Second World War, more American soldiers in the far east died of malaria than that killed by the human enemy. It still remains the number one public health problem in many countries. More than one million people die in Africa. In India alone 20 to 30 million people suffer from malaria every year. In spite of continuous advances in malariology, and advances in public health services, it is still causing havoc taking heavy toll of life and inflicting severe damage to the health of the people. Malaria is one of the most important causes of economic misfortune, engendering poverty, diminishing the quality of food supply, lowering the physical and intellectual standard of the nation. It also harms economic progress in every way.